The Effect of Silver Nano Particles on Candida Albicans and Streptococcus Mutans in Denture Acrylic Resins - Ahmad Ghahremanloo; Mohsen Movahedzadeh (Mashhad University of Medical Sciences, 2016)
Introduction: Denture stomatitis is a common complication in patients wearing dentures and preventing the proliferation of related microorganisms and their induced infections is noteworthy. The aim of the present study was to assess the antimicrobial effect of acrylic resins containing various concentrations of silver nanoparticles, on Candida albicans and Streptococcus mutans. Materials and Methods: In this in vitro study, the effect of four different concentrations of silver nanoparticles in 160 acrylic samples (10mm *4mm) on standard and hospital isolated strains of two different microorganisms were investigated. The samples were soaked (containing silver nanoparticles and control) in bacterial suspension and the antimicrobial tests were performed after 0, 1, 6 and 24 hours. Mean and standard deviation were used to describe the data and one-way variance analysis test was performed to compare groups. Results: Results have shown that in concentration of 2.5% the highest mean difference for standard S. mutans, after 24h of exposure was 540.0±14.4 (P